2011
DOI: 10.1093/aje/kwq426
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Mustard Gas Exposure on Incidence of Lung Cancer: A Longitudinal Study

Abstract: Sulfur mustard, an agent used in chemical warfare, is an alkylating substance with carcinogenic potential. However, the precise long-term carcinogenic effects of mustard gas are unclear. Since 1952, the authors have conducted health surveys of former workers who were employed from 1929 to 1945 in a poisonous gas factory in Okuno-jima, Hiroshima, Japan. This prospective study was undertaken from 1952 to 2005 to examine the incidence of lung cancer among the workers who were exposed to mustard gas (n=480), lewis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 22 publications
0
16
0
Order By: Relevance
“…In addition, the eyes and the respiratory tract are other major targets of SM-induced toxicity (Kehe et al 2009). Long-term effects include impaired wound healing, chronic suppression of the immune system, and carcinogenesis, such as the development of lung cancers (Balali-Mood and Hefazi 2005;Doi et al 2011;Hosseini-khalili et al 2009;Mukaida et al 2017). Moreover, early on, it was recognized that SM suppresses hematopoiesis and causes bone marrow depletion and leukopenia (Balali-Mood and Hefazi 2005;Krumbhaar 1919;Pappenheimer and Vance 1920;Vedder 1925).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the eyes and the respiratory tract are other major targets of SM-induced toxicity (Kehe et al 2009). Long-term effects include impaired wound healing, chronic suppression of the immune system, and carcinogenesis, such as the development of lung cancers (Balali-Mood and Hefazi 2005;Doi et al 2011;Hosseini-khalili et al 2009;Mukaida et al 2017). Moreover, early on, it was recognized that SM suppresses hematopoiesis and causes bone marrow depletion and leukopenia (Balali-Mood and Hefazi 2005;Krumbhaar 1919;Pappenheimer and Vance 1920;Vedder 1925).…”
Section: Introductionmentioning
confidence: 99%
“…SM exposure has also been associated with the development of cancer. In a Japanese cohort followed for decades after industrial exposure to SM and other toxins, the age range for the onset of lung cancer was accelerated by approximately 4 years (Doi et al, 2011). On autopsy of veterans dying approximately 20 years after SM exposure, the main pulmonary findings were fibrosis, infections, and malignant cellular infiltration (Taghaddosinejad et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…7 Also, association between chemical warfare and lung cancer was not well understood but many reports in the literature have confirmed that sulfur mustard may decreased the age at which people were at risk of developing lung cancer and also increase the rate of lung cancer in the victims. [8][9][10][11] In the acute phase, sulfur mustard which is an alkylating agent, may be rapidly results in bronchiolitis obliterans or "mustard lung" but the chronic effects of this type of chemical warfare poisoning in the victims remained to be depicted. 11 Only a few seconds of exposure to this relatively odorless gas is enough for developing the symptoms.…”
Section: Discussionmentioning
confidence: 99%